Educators' Perspective On The Progressivist Approach In Teaching Science Online - Jastine Kent E. Florungco; Dennis G. Caballes (International Journal of Asian Education, 2022)
Progressivism is the trend in the modern education system since it aims to focus and develop the skills and abilities of the learners. Educators play a vital role in the learning setup because they are the facilitator of learning in the class session. In the time when most schools employ online learning, problems arise as to how teachers can make every session student-centered. This qualitative study aims to provide ways as to how teachers can make an online class more interesting and engaging for the students. The teacher respondents mentioned that giving group works to students and letting them engage in collaborative learning is beneficial since the objectives are being met and at the same time, learners are enjoying. It is also recognized that the internet connection is the main problem in this set-up, while it was also mentioned that games help maintain the interest of these learners.